PLANTING NOBLE MORALS IN LEARNING AT IT AL-MUNADI MEDAN JUNIOR HIGH SCHOOL - M. Iqbal; Novy Ayu Trisna (Universitas Dharmawangsa, 2021)
Based on the above description, the author can draw conclusions related to the cultivation of noble morals in learning at Al-Munadi Medan JUNIOR HIGH SCHOOL, as follows: a) What teachers face in the cultivation of noble morals is from the environment and place where students make friends, just how a student performs and takes the positive side of every noble moral learning to guide students on the cultivation of noble morals. b) The way teachers instill noble morals in learning is: 1) Given an understanding of the importance of religion; 2) Assessing their efforts; 3) Paying attention to students in the cultivation of noble morals